Karakteristik Pasien dan Gambaran Indeks Platelet pada Pasien Leukemia Limfoblastik Akut di Rumah Sakit Al-Islam Kota Bandung Periode 2020-2022 - Amalia Salima; Yani Triyani; Sadeli Masria (UNISBA Press, 2024)
Abstract. Acute lymphoblastic leukemia (ALL) is the most common blood cancer in children in Indonesia. The latest data regarding the characteristics of ALL patients at Al-Islam Hospital Bandung City is currently not available. Apart from that, there are 27 blood parameters released by the hematology analyzer, but there are still values that have not been used optimally in helping to diagnose ALL, namely the platelet index. This study aims to determine the characteristics and features of platelet indices in acute lymphoblastic leukemia patients before and after chemotherapy. The method used is descriptive using medical record data from ALL patients aged 0–18 years for the period 2020–2022. This research was carried out at Al Islam Hospital Bandung during November 2023 and the data collection technique used total sampling. The data is processed using Statistical Product and Service Solutions (SPSS) software. In this study, 1040 medical record data were obtained and 292 of them met the inclusion criteria. The most frequent cases of ALL occurred in 2022 with 384 patients, aged 18 months–10 years in 721 patients (79%), male gender in 569 patients (55%), type of diagnosis was remission in 149 patients (51%). In addition, the hemoglobin level was 7.00–11.00 g/dL in 179 patients (63%), the leukocyte count was <10,000 mm3 in 209 patients (73%), and the platelet count was >100,000 mm3 in 181 patients (65%). In conclusion, the characteristics of most ALL patients are male, age 18 months–10 years, and type of diagnosis in remission. Abstrak. Leukemia limfoblastik akut (LLA) merupakan kanker darah yang paling banyak terjadi pada anak di Indonesia. Data terbaru mengenai karakteristik pasien LLA di RS Al-Islam Kota Bandung saat ini belum tersedia. Selain itu, terdapat 27 parameter darah yang dikeluarkan hematology analyzer, tetapi masih ada nilai yang belum digunakan secara optimal dalam membantu penegakan diagnosis LLA yaitu indeks platelet. Penelitian ini bertujuan mengetahui karakteristik dan gambaran indeks platelet pada pasien leukemia limfoblastik akut sebelum dan sesudah kemoterapi. Metode yang digunakan adalah deskriptif yang menggunakan data rekam medik pasien LLA usia 0–18 tahun periode tahun 2020–2022. Penelitian ini dilaksanakan di Rumah Sakit Al Islam Bandung selama bulan November 2023 dan teknin pengambilan data menggunakan total sampling. Data tersebut diolah menggunakan perangkat lunak Statistical Product and Service Solutions (SPSS). Pada penelitian ini didapatkan 1040 data rekam medik dan yang memenuhi kriteria inklusi sebanyak 292. Kasus LLA paling sering terjadi pada tahun 2022 sebanyak 384 pasien, usia 18 bulan–10 tahun pada 721 pasien (79%), jenis kelamin laki-laki 569 pasien (55%), jenis diagnosis remisi pada 149 pasien (51%). Selain itu, kadar hemoglobin 7,00–11,00 g/dL pada 179 pasien (63%), jumlah leukosit <10.000 mm3 pada 209 pasien (73%), dan jumlah platelet >100.000 mm3 pada 181 pasien (65%). Simpulan, karakteristik pasien LLA terbanyak laki-laki, usia 18 bulan–10 tahun, dan jenis diagnosis remisi.